2014
DOI: 10.1002/elps.201400012
|View full text |Cite
|
Sign up to set email alerts
|

Capillary electrophoresis for the analysis of the effect of sample preparation on early stages of Aβ1–40 aggregation

Abstract: Aggregation of the amyloid-β protein (Aβ) contributes to the neurodegeneration characteristic of Alzheimer’s disease. Of particular importance are the early stages of aggregation, which involve the formation of soluble oligomers and protofibrils. In these studies, we demonstrate the potential for CE with UV detection using a polyethylene oxide separation matrix to identify the evolution of various oligomeric species of Aβ1–40. To demonstrate the efficacy of this technique, UV-CE was utilized to compare two met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 46 publications
2
12
0
Order By: Relevance
“…A previous study of the aggregation of HFIP treated Ab 1-40 using UV-CE by Pryor et al reported an initial increase in the smaller aggregates before a decrease was observed. 34 A similar pattern can be observed in Fig. 3(a) where the <7 mers species remain high or even increase in concentration, followed by a significant decrease at around 12-18 h of aggregation.…”
Section: B Uv-ce With and Without Fasssupporting
confidence: 82%
See 3 more Smart Citations
“…A previous study of the aggregation of HFIP treated Ab 1-40 using UV-CE by Pryor et al reported an initial increase in the smaller aggregates before a decrease was observed. 34 A similar pattern can be observed in Fig. 3(a) where the <7 mers species remain high or even increase in concentration, followed by a significant decrease at around 12-18 h of aggregation.…”
Section: B Uv-ce With and Without Fasssupporting
confidence: 82%
“…A 1 mg lyophilized powder of Ab 1-42 sample from AnaSpec (San Jose, CA, USA) was pretreated using 1,1,1,3,3,3-hexafluoro-2-propanol (HFIP) as described by Pryor et al 34 The pretreated sample was separated into vials, dried, and stored at À80…”
Section: A Ab Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…CE with UV detection was employed for the analysis of several Aβ monomers [16,17], for the separation of monomers and transient soluble oligomers of Aβ 1-40 or 1-42 using neutral saline background electrolyte [18][19][20][21] or a polymeric separation matrix [22]. Moreover, CE-UV allowed the separation of monomers, large aggregates (migrating as wide peak) and fibrils (migrating as sharp peaks or spikes) [23].…”
Section: Introductionmentioning
confidence: 99%